MATHEMATICAL MODELING OF CORRUPTION DYNAMICS: EXAMINING THE REINTEGRATION OF FORMERLY CORRUPT INDIVIDUALS - Solomon Isa, Rwat; Emmanuel, Sabastine; Danat, Nanle Tanko; Tsok, Samuel Hwere (FUDMA JOURNAL OF SCIENCES, 2023)
Corruption is a global menace that undermines the foundations of societies, including the rule of law, fairness, human rights, democracy, and economic growth. This research aims to comprehensively understand the dynamics of corruption and explore strategies for its prevention and control. Specifically, it focuses on the re-integration of individuals who have recovered from corrupt practices back into the population. By evaluating the effectiveness of rehabilitation programs, the potential for relapse, and the influence of societal support systems, the study seeks to determine whether the re-integration of formerly corrupt individuals contributes to a reduction in corruption or reintroduces corrupt practices. The research employs mathematical models and analyses to investigate the transmission of corruption within the population. It examines the stability properties of uncontrolled corruption models and explores the effectiveness of different combinations of corruption prevention measures. By studying these factors, the research aims to gain insights into the underlying dynamics of corruption and identify strategies that can effectively mitigate its prevalence. The findings of this research will contribute to a deeper understanding of corruption dynamics and provide valuable insights for designing intervention programs. By informing policies and strategies, this research aims to combat corruption and foster a society that upholds integrity and ethical practices. The goal is to create a framework that supports the eradication of corruption and the promotion of transparency and accountability in all aspects of society.
Keywords: Corruption; Dynamics; Prevention; Reintegration; Strategies